2017
DOI: 10.1016/j.ijpharm.2017.09.044
|View full text |Cite
|
Sign up to set email alerts
|

Milling solid proteins to enhance activity after melt-encapsulation

Abstract: Polymeric systems for the immobilization and delivery of proteins have been extensively used for therapeutic and catalytic applications. While most devices have been created via solution based methods, hot melt extrusion (HME) has emerged as an alternative due to the high encapsulation efficiencies and solvent-free nature of the process. HME requires high temperatures and mechanical stresses that can result in protein aggregation and denaturation, but additives and chemical modifications have been explored to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Therefore, we also formulated the CPMV vaccine candidates as a slow-release polymer implant prepared by hot-melt extrusion, a highly scalable process technology suited for epidemic or pandemic response. Our previous research showed that VNPs can withstand hot-melt extrusion, yielding slow-release polymer melts that release structurally intact and biologically active VNPs; in previous work, virus-like particles (VLPs) derived from a bacteriophage were considered; here, we apply these technologies to the plant virus CPMV.…”
mentioning
confidence: 99%
“…Therefore, we also formulated the CPMV vaccine candidates as a slow-release polymer implant prepared by hot-melt extrusion, a highly scalable process technology suited for epidemic or pandemic response. Our previous research showed that VNPs can withstand hot-melt extrusion, yielding slow-release polymer melts that release structurally intact and biologically active VNPs; in previous work, virus-like particles (VLPs) derived from a bacteriophage were considered; here, we apply these technologies to the plant virus CPMV.…”
mentioning
confidence: 99%
“…Additional loading above these critical concentrations led to a decreased toughness improvement, which was likely due to aggregation of spores within the matrix. High temperature and shear applied during the HME process, together with high spore concentration, has been found to induce the aggregation of spores in a TPU matrix 51 . Interestingly, the critical spore concentration of BC TPU HST (0.8 w/w%) was higher than BC TPU WT (0.4 ∼ 0.6 w/w%), while the ultimate toughness improvement of BC TPU HST (37%) was also more remarkable than that of BC TPU WT (25%) at their respective critical spore concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…(e) End‐point titers of anti‐Qβ IgG indicating the implanted PLGA/Qβ devices immunize as effectively as repeated Qβ administration. Adapted with permission from Duque et al (2018), Ghalanbor et al (2010), P. W. Lee, Maia, and Pokorski (2017), P. W. Lee, Shukla, et al (2017), and Lee et al (2015)…”
Section: Implantable Devices For Sustained Protein Delivery—hydrogel or Amorphous Solid Dispersion?mentioning
confidence: 99%
“…PEGylation can result in reaction products that can be difficult to separate and require extensive filtration or chromatography to remove unreacted components, and cause low yield and waste (Freitas & Abrahão‐Neto, 2010). Lee, Maia, and Pokorski (2017) then sought an alternative method of using milling to reduce the size of protein before HME, making it easier for proteins to homogeneously disperse in a PLGA substrate. The implants were manufactured with a self‐built syringe extruder heating at 95°C for 10 min.…”
Section: Implantable Devices For Sustained Protein Delivery—hydrogel or Amorphous Solid Dispersion?mentioning
confidence: 99%